Biomechanics and Performance of Single-Leg Vertical and Horizontal Hop in Adolescents Post-Anterior Cruciate Ligament Reconstruction - Eva M. Ciccodicola; Alison M. Hanson; Shawn E. Roberts; Mia J. Katzel; Tishya A. L. Wren (Biomechanics)
Background/Objectives: Single-leg hops are used to determine return to sport after anterior cruciate ligament reconstruction (ACLR). Adult studies support the use of single-leg vertical hop (SLVH) due to higher power generation from knee extensors compared to single-leg horizontal hop (SLHH). Research in children is lacking. This study examines the differences between SLVH and SLHH in pediatric athletes post-ACLR. Methods: We retrospectively examined patients with ACLR who performed SLHH and SLVH on each limb while kinematics and kinetics were collected with a Vicon motion capture system. The limb symmetry index (LSI) for hop distance/height was used to classify the patients as asymmetric (LSI < 90%) or symmetric (LSI ≥ 90%). Biomechanics were compared between limbs and as a function of group using linear mixed models. Results: Among the 19 patients (15 female; age 16.3 years; 9.2 months post-surgery), approximately half were classified as asymmetric (10/19 = 53% for SLHH; 9/19 = 47% for SLVH). During SLHH, the symmetric patients’ uninjured limb produced less power and a shorter hop. During SLVH, the symmetric patients produced more power and hopped higher bilaterally. Regardless of symmetry, the reconstructed knee was offloaded (p ≤ 0.03) and contributed less to power absorption (p ≤ 0.02). Conclusions: SLVH height symmetry may be a better indicator of knee recovery than SHLH distance in pediatric athletes. However, knee offloading is common even when symmetry is achieved.